Cover Image. (14th March 2022) - Figueira, Rebeca Lopes; Antounians, Lina; Zani‐Ruttenstock, Elke; Khalaj, Kasra; Zani, Augusto
Abstract : The cover image is based on the Review Fetal lung regeneration using stem cell‐derived extracellular vesicles: A new frontier for pulmonary hypoplasia secondary to congenital diaphragmatic hernia by Rebeca Lopes Figueira et al., https://doi.org/10.1002/pd.6117 .